OCB in Banking: A Mediating Model of Psychological Capital, Workload, and Job Satisfaction - M. Arief Wahyudi Ginting; Rahmi Fahmy; Harif Amali Rivai (Journal Publicuho, 2024)
Maron Tourism Village Management is an innovative program implemented by Village-This study aims to evaluates the effects of psychological capital and workload on OCB, and the mediating contribution of job satisfaction in Bank Indonesia representative area West Sumatera and Pematang Siantar. A purposive sampling technique with single criteria was used for 82 permanent bankers. Then, their responses to the online questionnaires were proposed and analysed by assisting Smart-PLS Sofware's latest version with the technique of Structural Equation Model (SEM) and path-analysis in two-tail criteria. The result shows that all relationships were tested can be stated in line with research expectations.